Development in the Global South at risk: Economic and social effects of the COVID-19 pandemic in developing countries - Gabriele Tondl (Austrian Foundation for Development Research (ÖFSE), 2021)
Developing countries (DCs) encounter the COVID-19 pandemic under distinctly different preconditions than high income countries. With a young population and permanently challenged by major infectious diseases like malaria and TB, but insufficient health infrastructure and poor public administrative structures, DCs are meeting particular problems to contain the spread of the COVID-19 pandemic. This paper wishes to show how dependence on export markets, disruption of supply chains, decline in remittances and containment measures have resulted in a major output drop in DCs. With a large informal sector, unstable employment contracts and little public social support, the population in DCs is hard hit by income losses so that poverty in DCs has grown rapidly. Three issues arise: First, what are the prospects of DCs to stop further waves of the COVID-19 disease? Second, why has the COVID-19 pandemic hit the economy of DCs so hard? Which role play dependency and trade specialisation in this context and will the trade patterns of DCs change in consequence of the COVID-19 pandemic? Third, how has poverty and human tragedy re-emerged in DCs in the course of the COVID-19 crisis and will it ruin the basis of future development? These issues will be discussed using the most recent data and academic literature available. The major conclusion of this paper is that DCs are disproportionately suffering from the economic and human consequences of the COVID-19 pandemic. To mitigate this miserable situation, they will need suitable, well-designed assistance from the Global North and international institutions.
Keywords: 330; COVID-19; Developing Countries; Supply Chains; Poverty; Inequality